(untitled) (Altre Modernità, 2014)
Giovanni Paolo Marana’s epistolary novel, entitled l’Espion du Grand-Seigneur and published for the first time in the 1680s, was a pioneering work of a genre that was to flourish much later, namely spy story. The story features an Arab who comes to Paris in 1637 and spends the next 45 years collecting information about French government’s activity without being ever identified by French counter-intelligence. The main character was an undercover agent of a Muslim empire, who watched Christians with contempt - and yet the book that pretended to be just a bunch of his letters, accidentally found and translated from Arabic by Marana, was a bestseller in late seventeenth- and then eighteenth-century Western Europe. The paper presents the fates of the work and discusses the reasons of its huge success. Apart from the fact that the novel was written in a brilliant style, and published at the time when the ongoing Habsburg-Turkish war had triggered intensive interest in the Muslim East, one of these reasons was the fact that it was published in the time when in France a modern police force was created. Its tasks included collecting information about political opinions, religious practices and intimate lives of the Sun King’s subjects. The new feeling of being observed by the government’s men and informers certainly prepared the ground for the success of the first spy story of the West.